Meningkatkan Kemampuan Menyimak (Listening) Siswa Melalui Media Film Berbahasa Inggris - Sitepu, Khairan Nisa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Nowdays, learning media has developed very well in various types, one of which is media in improving students' listening skills. One example of media that can be used is English films. By using this film media many benefits will be obtained by students such as: students can learn good English pronunciation directly from films that are shown, students can add new vocabulary, students can learn good and correct grammar and also students can practice their listening skills. In addition, this film media can make students more active in attending classes, not boring and interesting so that learning can run well. The purpose of this study is to find out how effective the use of films is in improving students'listening skills in the field of English language studies, and also to find out students' perspectives on the use of films as learning media. In the research conducted, the researcher used the literature study method by collecting some data from various related journals to be reviewed in collecting data. The final result ofthis research is that the use of English films in improving students' listening skills is very effective. According to the students' perspective, the use of this film is very helpful for them in learning listening skill.